2009
DOI: 10.1007/978-3-7643-8336-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity: damage to DNA and its consequences

Abstract: A genotoxin is a chemical or agent that can cause DNA or chromosomal damage. Such damage in a germ cell has the potential to cause a heritable altered trait (germline mutation). DNA damage in a somatic cell may result in a somatic mutation, which may lead to malignant transformation (cancer). Many in-vitro and in-vivo tests for genotoxicity have been developed that, with a range of endpoints, detect DNA damage or its biological consequences in prokaryotic (e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(76 citation statements)
references
References 94 publications
(62 reference statements)
1
72
0
3
Order By: Relevance
“…A germ cell mutagen is an agent that induces (heritable) mutations in germ cells. Detection and characterization of DNA adducts formed by the germ cell mutagens provide evidence to the etiology of the developmental abnormalities and cancer induction in the offsprings (Phillips and Arlt 2009). Our data showed that the wastewater constituents were capable of interacting with the genetic processes involved in spermatogenesis in mice.…”
Section: Discussionmentioning
confidence: 72%
“…A germ cell mutagen is an agent that induces (heritable) mutations in germ cells. Detection and characterization of DNA adducts formed by the germ cell mutagens provide evidence to the etiology of the developmental abnormalities and cancer induction in the offsprings (Phillips and Arlt 2009). Our data showed that the wastewater constituents were capable of interacting with the genetic processes involved in spermatogenesis in mice.…”
Section: Discussionmentioning
confidence: 72%
“…Cancer is a multistage process characterized by a series of genetic alterations that result in the loss of cellular growth, proliferation, and differentiation control [8]. These genetic alterations include somatic mutations in DNA that may arise as a result of the action of either endogenous (e.g., reactive oxygen species) or exogenous (e.g., environmental carcinogens) agents [9].…”
Section: Dnamentioning
confidence: 99%
“…There is a wide variety in de novo human germline mutations, and these can include duplications or deletions of various size, as well as alterations in the number of chromosomes (Arnheim & Calabrese, 2009). The frequency of de novo mutations in germ-line cells increases with parental age, and can also be caused by environmental factors such as radiation exposure (Sasaki, 2006), genotoxic chemicals (Phillips & Arlt, 2009), or congenital viral infections (Ansari & Mason, 1977;Fortunato & Spector, 2003;Nusbacher et al, 1967;Vijaya-Lakshmi et al, 1999).…”
Section: Heritability Of Complex Human Diseasesmentioning
confidence: 99%